Prisoner Exchange in the Russian-Ukraine Conflict: A Juridical Analysis Under International Law - Kasyfil'Aziz, Muhammad; Yusnita, Ummi (Fakultas Hukum, Universitas Krisnadwipayana, 2024)
The background of this research is rooted in the ongoing conflict between Russia and Ukraine, which has resulted in significant casualties on both sides, affecting both military personnel and civilians. The conflict has also led to the capture of numerous prisoners of war by each side. Given these circumstances, the potential for a prisoner exchange agreement between the two nations has become increasingly relevant. This research analyzes the principles of international law governing prisoner exchanges during active conflicts. Employing normative legal research methods, this study reviews the application of various international laws and conventions, specifically focusing on the Geneva Conventions of 1949. The findings of this research suggest that while the Geneva Conventions’ provisions on prisoner exchange remain applicable, their implementation in the current conflict is hindered by a lack of trust between the two countries. This distrust may necessitate reliance on extradition frameworks to address humanitarian law violations.